1984
DOI: 10.1002/j.1460-2075.1984.tb02174.x
|View full text |Cite
|
Sign up to set email alerts
|

A transposon-like structure related to the delta-endotoxin gene of Bacillus thuringiensis.

Abstract: A DNA segment (Th‐sequence) has been found in several strains of Bacillus thuringiensis. This Th‐sequence [3 megadaltons (Md)] induces adjacent deletions when it is located in the pAM beta 1 plasmid derived from Streptococcus faecalis. Electron microscopic examination of reannealed single strands of one plasmid (pMT9) carrying such a deletion revealed that the Th‐sequence corresponds to a single‐stranded loop (2.8 Md) bounded by a short double‐stranded stem (less than 0.2 Md). Southern blotting experiments est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
43
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 16 publications
(22 reference statements)
0
43
0
Order By: Relevance
“…Lereclus et al (16) reported a model for the structural organization of Tn4A43 (4.2 kb), a crystal gene (ca. 3.7 kb) and two sets of invertsd repeats, IRI (1.7 kb) and IR2 (2.1 kb), on plasmid pBT42, indigenous to the berliner strain of B. thuringiensis.…”
Section: Tn917mentioning
confidence: 99%
See 2 more Smart Citations
“…Lereclus et al (16) reported a model for the structural organization of Tn4A43 (4.2 kb), a crystal gene (ca. 3.7 kb) and two sets of invertsd repeats, IRI (1.7 kb) and IR2 (2.1 kb), on plasmid pBT42, indigenous to the berliner strain of B. thuringiensis.…”
Section: Tn917mentioning
confidence: 99%
“…They found that these genetic elements were arranged to form a composite transposon-like element on the plasmid. Tn4430 and the crystal gene were separated by one copy of IRI, and these three elements were flanked on each side by another copy of IRI (16).…”
Section: Tn917mentioning
confidence: 99%
See 1 more Smart Citation
“…has been extensively studied (19,20,25). In several cases, the crystal gene has been found to be flanked by two sets of inverted repeat (IR) sequences and also to be associated with a transposable element, Tn4430 (24,25).…”
mentioning
confidence: 99%
“…The sizes of the loops were estimated as 4.49 ± 0. 37 (23,25). The scale used is half of that used for pRX70.…”
mentioning
confidence: 99%